Diseases of Pleura - Stojšić, Jelena (IntechOpen, 2020)
Pleural diseases are usually accompanied by pulmonary or nonpulmonary (heart, kidney, thyroid, systemic) diseases. Rarely, pleural diseases are solitary lesions. Pleural effusions are frequent manifestations of pleural diseases. Their treatment depends on the cause of effusion. Tuberculous and nontuberculous inflammation of pleura cause effusion as well as benign and malignant tumors. Talc treatment is one of the modalities of therapy for pleural effusions. Asbestosis is still the leading cause of pleural tumors. A solitary fibrous tumor of pleura is a mesenchymal tumor with various morphological patterns but with a consistent immunophenotype. A high proliferative index requires frequent follow-up because of possibe relapse and mandatory oncological treatment. A pleural malignant mesothelioma is aggressive and is the most frequent tumor of mesothelial origin. This book provides readers with a better understanding of pleural diseases, their etiology, diagnosis, and therapy